4SCAR‐GD2‐modified T‐cell therapy in neuroblastoma with MYCN amplification: A case report with over 4‐year follow‐up data. Issue 1 (17th March 2020) - Xu, Xiao; Zhao, Wen; Yue, Zhixia; Qin, Maoquan; Jin, Mei; Chang, Lung‐Ji; Ma, Xiaoli
Abstract: Introduction: Neuroblastoma (NB) is the most common extracranial solid tumor among children. The 5‐year event‐free survival rate for high‐risk (HR) NB is still poor, especially for patients with advanced NB with MYCN gene amplification. Chimeric antigen receptor T (CAR‐T) cell therapy is a new treatment for HR‐NB. Case presentation: A 55‐month‐old boy with stage IV HR‐NB received 4th‐generation CAR‐T cells that target disialoganglioside GD2, as consolidation maintenance treatment after intensive chemotherapy, surgery, and autologous stem‐cell transplantation. As of February 2019, his CAR‐T follow‐up time was 37.5 months, indicating prolonged survival. Cranial MRI and ultrasound showed no mass; 123 I‐metaiodobenzylguanidine ( 123 I‐MIBG) scan was negative. Conclusion: GD2‐CAR‐T cells may be an effective treatment option for NB patients with MYCN amplification.